(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
Electronic cash or cyber cash and virtual currency are all forms of digital currencies. Indeed, computers on the bitcoin network check for unauthorized attempts to alter trans actional records. The importance cannot be overstated, as virtually every human civili zation, every bank, council, and local library is based on a centralized or decentralized organizational structure. Bitcoin is a digital currency that is referred to as cryptocurrency because it is a form of electronic currency that relies on cryptographic techniques, the science of making and breaking codes, to prove identity and authenticity and to enforce read and write access to the bitcoin network. This paper examines the features of bitcoin, the stakeholders in it, the mining process, and the position of Central Bank of Nigeria. This paper will help new researchers to work on bitcoin and its integration challenges in the financial system.